The Heat and Momentum Transfers Relation in Channels of Plate Heat Exchangers - Kapustenko, P. O.; Arsenyeva, O. P.; Dolgonosova, O. (The Italian Association of Chemical Engineering, 2011)
The link between heat transfer intensity and hydraulic resistance of PHE channels is determined with the use of modified Reynolds analogy of heat and momentum transfer. The formula to estimate the share in total hydraulic resistance of pressure loss due to friction is proposed. The resulting model enables to calculate film heat transfer coefficients in PHE channels on a data of hydraulic resistance of the main heat transfer field. The calculations are compared with the available in literature experimental results on heat transfer in channels with cross corrugated walls. The good agreement confirms the assumptions made on deriving equation and existence in PHE channels of the analogy between heat and momentum transfer in proposed form.